Adverb in Indonesian - I Dewa Putu Wijana (Ranah: Jurnal Kajian Bahasa, 2022)
This paper is intended to describe the forms and meanings of adverb in Indonesian. Adverbs are “words” that function to specify or locate the proposition expressed within the clause. By this concept, I limit my attention to merely what the so called “extra clausal adverbs”, a categorical concept along with noun, adjective, verb, etc. This concept is fundamentally differentiated from “adverbials”, elements of  clause structure along with subject, predicate, object, etc. By using data collected through introspective methods and some extracted from Intisari, and after analyzing them using distributional analysis followed by its continuation techniques (permutation, paraphrase, and comparison), the reasearch found that Indonesian adverbs are formally constructed at least by four kinds of morphological process, i.e. conversion, affixation, reduplication, and compounding. As far as the semantic roles are concerned, they can mainly be classified into four types, i.e adverbs of manner and state, adverbs of modality, adverbs  of frequency and quantity, adverbs of time. Finally, the differences that hold among Indonesian adverbs belong to the same semantic types might be related to  degree of formality, intensity, politeness, and style of the utturances. AbstrakMakalah ini bertujuan untuk memerikan bentuk dan makna adverbia dalam bahasa Indonesia. Adverbia adalah kata-kata yang berfungsi untuk mengkhususkan atau melokasikan proposisi yang diungkapkan oleh sebuah klausa. Dengan konsep ini, penulis membatasi perhatian pada apa yang selama ini disebut adverbia ekstra klausal, konsep kategori yang sepadan dengan nomina, adjektiva, verba, dsb. Konsep ini secara fundamental dibedakan dengan adverbial, elemen struktur  klausa yang sepadan dengan subjek, predikat, objek, dsb. Dengan data yang dikumpulkan melalui metode introspektif dan beberapa di antaranya dikumpulkan dari Majalah Intisari, dan setelah menganalisisnya dengan metode distribusional disertai dengan teknik lanjutannya (permutasi, parafrase, dan perbandingan), penelitian menemukan bahwa adverbia bahasa Indonesia sekurang-kurangnya dikonstruksi secara formal dengan proses konversi, afiksasi, reduplikasi, dan pemajemukan. Sementara itu berdasarkan peran semantisnya adverbia bahasa Indonesia dapat dibedakan menjadi adverbia cara dan keadaan, modalitas, keseringan dan kuantitas, dan waktu. Akhirnya adverbia-adverbia yang tergolong ke dalam tipe semantik yang sama memiliki perbedaan dalam hal tingkat keformalan, intensitas, kesantunan, dan ragam tuturan.